Uniparental progeny in Neurospora crassa - Edward G. Barry (Fungal Genetics Reports, 1996)
Seven ascospores from one ascus of a biparental mating were all the genotype of one parent. Neither mating type substitution nor mutation of the mating type explain this aberrant result.